2019
DOI: 10.1177/2042098619859996
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus after discontinuation of cetirizine

Abstract: Background: Intense pruritus or itching emerging after discontinuation of cetirizine has been the subject of postmarketing reports submitted to the U.S. Food and Drug Administration (FDA), published in the medical literature, and discussed on the internet. To better understand and further investigate this adverse event, we analyzed cases of pruritus occurring after discontinuation of cetirizine in the FDA Adverse Event Reporting System (FAERS) database and medical literature. Methods: We conducted a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Although symptomatic therapies are the first line of action for patients with allergic diseases, their benefit comes with several downsides. Patients have to be treated continuously and upon treatment discontinuation, symptoms commonly relapse ( 19 ). Some of the symptomatic anti-allergic drugs have undesirable side effects such as somnolence in the case of first generation antihistamines ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although symptomatic therapies are the first line of action for patients with allergic diseases, their benefit comes with several downsides. Patients have to be treated continuously and upon treatment discontinuation, symptoms commonly relapse ( 19 ). Some of the symptomatic anti-allergic drugs have undesirable side effects such as somnolence in the case of first generation antihistamines ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus also seems to be effective for longer periods of time after treatment has stopped, whereas stopping the usage of OTC medications can lead to a rebound in symptoms and withdrawal reactions such as severe itching. 7 Astragalus also has disadvantages, particularly as it has not been extensively studied within human clinical trials. Matkovic et al discussed that astragalus is effective because it lowers IgE and eosinophil levels.…”
Section: Astragalus Membranaceusmentioning
confidence: 99%
“…Furthermore, consistently utilizing one antihistamine can lead to the development of tolerance to the treatment and even withdrawal upon stopping. 7 As such, this paper will focus on three alternatives to current over-the-counter (OTC) pharmacotherapy, butterbur, astragalus membranaceus, and tinospora cordifolia, to determine the potential of herbal treatments of allergic rhinitis, especially since they are often less expensive and incur fewer side effects. A review of various studies and trials will be conducted to determine the efficacy of the herbs and to analyze whether or not it is advantageous to OTC medications.…”
Section: Introductionmentioning
confidence: 99%
“… 13 However, after drug withdrawal, the allergy is easy to recur, which will induce itching again. 14 Another drug, bifid triple viable capsules, is composed of Bifidobacterium, Lactobacillus and Enterococcus , which has been shown to be effective against diarrhea caused by GMB disturbances or enteritis and has been approved by the State Food and Drug Administration of China as a nonprescription drug. 15 Pharmacological studies have shown that bifid triple viable, given orally, can alleviate intestinal inflammations via regulating beneficial and harmful flora like Lactobacillus and Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%